Fetus in Fetu: Report of Two Cases - Goyal, Ram Babu (EL-MED-Pub, 2014)
Fetus-in-fetu (FIF) is a rare and interesting entity characterized byincorporation of a malformed, monozygotic, diamnionic parasitic twin into the body of other normal twin partner. FIF is differentiated from teratoma by its embryological origin, its unusual location in the retroperitoneal space and the presence of vertebral column (axis) often with appropriate arrangement of other organs or limbs around this axis. We report two cases of FIF. Our first case presented at 18 months, while second at 9 year of age. FIF derived their blood supply directly from aorta in both the cases.Our FIF had distinct fetoid features, well developed axial skeleton with a complete spinal column, trunk, intestinal loops, four limbs, well developed fingers and toes, male external genitalia and abundant scalp hairs. Their weightwas 600 grams and 800 grams, respectively. Postoperative period was smooth and on long-term follow up no evidence of recurrence was seen in both the patients.